Aplikasi Sosiologi Pengetahuan dalam Studi Hadis: Tijauan Kronologis-Historis terhadap Perumusan Ilmu Mukhtalif al-hadis asy-Syafi'i - Muhammad Irfan Helmy (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2020)
Enriching the perspective of the science of hadith can be done with the study of hadith which focuses on the sociological-historical dimension. One of studies that use a sociological-historical perspective is the science of Mukhtalif al-Hadith formulated by al-Shafi'i. The sociological approach to knowledge is used in this article to uncover the sociological dimension of the formation of mukhtalif al-hadith. The results of this approach reveal that the formulation of the science of mukhtalif al-hadith al-Shafi'i is started from the thoughts about the hadith during al-Shafi'i, especially those which are destructive to the position of hadith. In observing the sociology of knowledge, the science of mukhtalif al-Hadith formulation of al-Syafi'i must be open in order to create new method contributions in the meaning of mukhtalif hadiths.